So, we know that the quadratic formula is x=-b+- the square root of b^2-4ac and all of this divided by 2a. You might be like "wow, where did all of these come from?" It is actually really easy. So, let's take your first equation: 2x^2-19x+24=0. So, let us look at the standard form for a quadratic formula: a^2+b+c=0. Now, If you look at the normal equation and the standard form for a quadratic, you will see that they are alike. Now, just match the letter with the number: a=2, b=-19, and c=24. Now that you know what each letter represents, you can plug everything into the equation x=-b+- the square root of b^2-4ac and all of this divided by 2a.